IMPLEMENTASI PENDEKATAN OPEN-ENDED TERHADAP PEMECAHAN MASALAH MATEMATIKA DI KELAS V SDN CEWENG JOMBANG - Lestari, Dyah Ayu; Basir, Udjang Pairin M.; Susilo, Claudya Zahrani (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
This study aims to determine the ability of mathematical problem solving before or after the application of the open-ended approach and student’s responses during learning. The techniques used in collecting data were interviews, questionnaire tests, and documentation. This type of research is quantitative with experimental design, statistical techniques are used to analyze the research results. The results of the study can be seen with the results of the pretest and posttest student’s abilities. The ability of students showed an average difference between the pretest and posttest scores of 36.71 and 80.81 and the Fcount was 122.927. So the conclusion is the problem solving ability of students has a significant difference and tends to increase. As well as a very positive response shown by students with a percentage of 84.3%.